Design, implementation and evaluation of an in-context learning support program for first year education students and its impact on educational outcomes. - de la Harpe, Barbara I. (Curtin University, 1998)
This research was concerned with furthering theoretical and practical understanding of student learning at university through a longitudinal, cross-sectional, in-depth study of first year students in a specific learning context, namely Educational Psychology. The main aim of the study was to investigate ways of assisting students to be effective learners. The particular role that affect played in learning and the relationship between learning behaviour and learning outcomes, was explored. A Conceptual Model of student learning incorporating student cognition, metacognition, motivation, affect and academic performance in a specific social and cultural context, underpinned the study. The study documented the design, implementation and evaluation - from both the students' and teacher's perspectives - of an in-context learning support program for first year students, using both quantitative and qualitative methodologies.The program was based on a theoretical framework which integrated cognitive, behavioural and social learning perspectives and focussed on increasing students' repertoire of learning strategies, promoting their higher level thinking and understanding, developing their metacognitive skills and managing their affect. It included an emphasis on student goal setting and time management, reading and writing strategies, learning for tests and exams, self-management, reflecting on and evaluating learning, and dealing with test anxiety.The main findings of the study were that providing in-context learning support was associated with positive changes in students' learning strategy use, motivational orientations, and affective reactions. Students valued teacher support and instructional strategies that promoted active learning. The instructor found that providing learning support was more challenging and rewarding than teaching content alone. The role of context - in particular, assessment tasks - in learning, was highlighted. The implications for teaching and learning were examined and the Conceptual Model was further refined. The research resulted in a more holistic and integrated perspective on learning support provision and on the role of cognitive, metacognitive, motivational and affective factors, and academic performance, in student learning.